Pengaruh Opini Audit, Kebijakan Hutang, dan Pertumbuhan Perusahaan terhadap Nilai Perusahaan - Idris Fadhillah; Mayar Afriyenti (Universitas Negeri Padang, 2021)
The purpose of this study is to analyze: (1) The effect of audit opinion on firm value. (2) The effect of debt policy on firm value. (3) The effect of company growth on firm value. The population in this study are all manufacturing companies listed on the Indonesia Stock Exchange (BEI) 2015-2019. While the sample collection technique in this study used purposive sampling technique with a sample size of 189 samples. The data analysis method used is multiple regression using SPSS 25 software. These results indicate that: (1) Audit opinion has a positive and significant effect on firm value with a significance of 0.007 <0.05. (2) Debt policy has a negative and significant effect on firm value with a significance of 0.001 <0.05. (3) Company growth has a positive and insignificant effect on firm value with a significance of 0.155> 0.05.